The short-term clinical efficacy of 79 cases of idiopathic membranous nephropathy - LI Xiao-wei; MEI Dong-dong; WANG Xian; HU Ben-jin (Linchuang shenzangbing zazhi)
Objective To observe the short-term clinical efficacy of different treatment regimens for idiopathic membranous nephropathy(IMN);and to explore the value of combination of moderate-dose hormones with cyclosporines for treatment of this disease.Methods A retrospective analysis was performed in 79 cases of patients with IMN diagnosed by renal biopsy in Fuyang People’s Hospital.Based on treatment regimens,the patients were divided into the symptomatic treatment group,the modified Ponticelli regimen group,and the moderate-dose hormones plus cyclosporines group Efficacy and adverse reactions were compared among the three groups after 6 months of treatment.Results(1) The quantity of urinary protein in the symptomatic treatment group was significantly lower than that in the modified Ponticelli regimen treatment group and in the moderate-dose hormones plus cyclosporines treatment group.(2)After treatment for 6 months,the urinary protein levels were significantly decreased in the three groups,while the plasma albumin was significantly increased.(3) After treatment for 6 months,the symptomatic remission rates in the symptomatic treatment group,in the modified Ponticelli regimen treatment group and in the moderate hormones plus cyclosporines treatment group were 72.0%,79.4% and 73.3% respectively,with no statistically significant difference between the three groups(P>0.05);but in the modified Ponticelli regimen treatment group,more patients had higher levels of hepatic enzymes(16%: 56.4%: 26.7%,P<0.05).Conclusions IMN patients with different clinical manifestations should choose different treatment regimens.The short-term clinical efficacy in the moderate-dose hormones plus cyclosporines treatment group is not significantly different from that in the modified Ponticelli regimen treatment group,but has smaller risk for transaminase liver impairment,and so may act as one of preferable treatment regiments for IMN.